The Influence of Electrophoretic Deposition (EPD) Parameters on SS430 Spinel Coated Characteristic - Lowrance, Yohannes; Azmi, Mohd Azham; Mohd Basar, Lufti; Abd Rahman, Hamimah (International Journal of Integrated Engineering, 2020)
The interconnect that is applied with protective coating which is (MnCO)3O4 spinel coated stainless steel is crucial to enhance solid oxide fuel cell (SOFC) performance. In this research, commercial manganese cobalt (MnCO)3O4 is used by electrophoretic deposition (EPD) method as a protective layer on ferritic stainless steel. Elemental energy dispersive X-ray spectroscopy (EDS) was examined for the spinel coated interconnect (MnCO)3O4. Scanning Electron Microscope (SEM) examines the surface morphology and coating thickness. The EPD (MnCO)3O4 spinel coated interconnect is carried out with 30V to 50V with duration of coating from 20s in an aqueous suspension. The best covering parameter can be determined by observing the deposition morphology and density of the EPD at 40V and 45V for 20s. This article examines the impact of voltage deposition. The objectives of these study is to obtain the best parameter for the interconnect coating while experimenting with the voltage. 78.8Î¼m with even and thick surface coating is the maximum deposition thickness achieved. Voltage deposition can therefore be concluded to affect the efficiency of the electrical conductivity of steel.